2011
DOI: 10.1017/s0001867800004961
|View full text |Cite
|
Sign up to set email alerts
|

How fast can the chord length distribution decay?

Abstract: Abstract. The modelling of random bi-phasic, or porous, media has been, and still is, under active investigation by mathematicians, physicists or physicians. In this paper we consider a thresholded random process X as a source of the two phases. The intervals when X is in a given phase, named chords, are the subject of interest. We focus on the study of the tails of the chord-length distribution functions. In the literature, different types of the tail behavior have been reported, among them exponential-like o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Further analytic calculations of intercept lengths, possibly aided by results from queuing theory, could include additional explicit formulas or improved approximations for other models of porous media, like Gaussian random fields, or cellular systems, like Voronoi tessellations . Going beyond the Poisson process and overlapping grains could help to deepen our understanding about the information content of the MIL analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Further analytic calculations of intercept lengths, possibly aided by results from queuing theory, could include additional explicit formulas or improved approximations for other models of porous media, like Gaussian random fields, or cellular systems, like Voronoi tessellations . Going beyond the Poisson process and overlapping grains could help to deepen our understanding about the information content of the MIL analysis.…”
Section: Discussionmentioning
confidence: 99%
“…During the final budget year, G. Samorodnitsky worked on the analysis of stochastic systems, concentrating on the effects of long range dependence and heavy tails. A surprising onclusion from the work "How Fast Can the Chord-Length Distribution Decay" with Demichel, Estrade and Kratz [4] is that in the threshold model for the bi-phasic media the effect of memory on the size of the phases is minimal. On the other hand, long memory has a major effect on the length of long strange segments and on the ruin probabilities for moving average processes, as was shown in a joint work with Ghosh, "Long strange segments, ruin probabilities and the effect of memory on moving average processes" [5].…”
Section: Names Of Personnel Receiving Masters Degreesmentioning
confidence: 99%
“…Vamvakos and Anantharam [VA98] showed that the long-range dependence of a point process is preserved by a leaky bucket flow control mechanism for data traffic. A study focused on the long-range dependence of multidimensional random sets is the recent work of Demichel, Estrade, Kratz, and Samorodnitsky [DEKS11], who studied whether random sets having power-law decaying chord length distributions, closely related to the covariance function of the random set, can be generated as a level set of a Gaussian random field-they found that in wide generality (merely assuming that the underlying Gaussian field is mixing), this is not possible.…”
Section: Is the Power-law Covariance Decay Of The Proposed Boolean Momentioning
confidence: 99%